(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
From last three decades of 20th century, women empowerment has become one of the important issues in development discourse. But, due to lack of voice, power and social barriers women are often unable to take advantage of opportunities to exercise their individual rights. Therefore, they need assets and capabilities to increase their wellbeing and security, as well as their self-confidence. In this context, interventionist policies of states and intermediate civil society groups plays transformative role in supporting people’s capabilities for their development. Since 1970s, the idea and practice of self help has developed world wide as a major social phenomenon for women empowerment. The SHG approach is basically a community development approach wherein the very poor members of a community are organized with a common objective for their socio-economic development and also for overall community development. So, the study has been designed empirically to focus on how Self Help Groups (SHGs) contribute in empowerment by providing entrepreneurship. Multi stage purposive random sampling technique has been used for selecting the study area and its sample. It reveals that SHGs leads to personal empowerment in terms of creating awareness in social issues but failed to transform into entrepreneurial or skill oriented income generation and mobilizing member in participating community issues for socio-economic empowerment.